2008
DOI: 10.1590/s0100-879x2008000800016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gender on psychomotor vigilance task performance by adolescents

Abstract: During adolescence, the sleep phase delay associated with early school times increases daytime sleepiness and reduces psychomotor performance. Some studies have shown an effect of gender on psychomotor performance in adults and children. Males present faster reaction times (RT) compared with females. The aim of the present study was to evaluate the influence of gender on Palm psychomotor vigilance task (PVT) performance in adolescents. Thirty-four adolescents (19 girls, 13 to 16 years old) attending morning sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 26 publications
3
14
2
1
Order By: Relevance
“…That is, the EPS intervention did not help them change their sleep patterns. The sleep patterns and sleep deprivation of this sample of Brazilian adolescents were similar to those observed in other studies upon adolescents from Brazil and other countries (LeBourgeois et al 2004;Gaina et al 2005;Hansen et al 2005;Gibson et al 2006;Beijamini et al 2008;Loessl et al 2008).…”
Section: Discussionsupporting
confidence: 85%
“…That is, the EPS intervention did not help them change their sleep patterns. The sleep patterns and sleep deprivation of this sample of Brazilian adolescents were similar to those observed in other studies upon adolescents from Brazil and other countries (LeBourgeois et al 2004;Gaina et al 2005;Hansen et al 2005;Gibson et al 2006;Beijamini et al 2008;Loessl et al 2008).…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies (Beijamini et al, 2008) have reported differences in mean RT between the sexes and in their approach to the task, particularly regarding the The low number of practice trials, combined with the results from the main study, add further evidence to the device's potential; results suggest that for this particular sample, time-consuming testing in isolation is not necessary. The implication of this finding is a potential reduction in the impact of PVT assessment on the classroom learning environment, which could result in more interest from educational institutions and staff members in being involved in future studies.…”
Section: Discussionsupporting
confidence: 55%
“…Both vigilance performance [ 17 ] and cardiovascular fitness [ 18 ] seem to be influenced by gender. However, while some studies have investigated the physical benefits of regular soccer participation in male adolescents [ 5 , 6 ], no study has investigated this relationship in female adolescents.…”
Section: Introductionmentioning
confidence: 99%